A Survey on the Teachers' Strategies in Teaching Vocabulary at The Seventh Grade Students of SMP Level in Letti Island - Satiawy, Ram; Anaktototy, Karolis; Meyer, Fredi (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2022)
This study was aimed at investigating teachers’ strategies in teaching vocabulary at the seventh grade of junior High Schools in Letti Island. The subject of the research was two English teachers at a Junior High school in Letti Island. The research explored the data about the strategies in teaching vocabulary implemented by English teachers at the Seventh grade SMP level in Letti Island.This quantitative research was conducted by using survey method in which the data were collected through interview and questionnaire.The finding in this study showed that the teachers applied several strategies in teaching vocabulary in the classroom, such as listen and do, listen and repeat, question and answer, substitution, listen and identify, concept mapping, spot the difference, and label the picture. The teachers strongly agree that vocabulary strategy can help the students to be more proactive and make them learn English more easily. The teachers also believed that vocabulary strategy could attract students’ interest in learning English vocabulary so they could perform better in front of the class when expressing their ideas and be more creative in learning vocabulary. The teachers also positively perceived the use of teaching vocabulary strategies for promoting foreign language acquisition.